An empirical examination of North-South linkages. - Ong, Seng Leong. (2008)
The purpose of this study is to test the level of interconnectedness and interdependence. The Engle-Granger-Yoo 3-step approach was used to search for a cointegration relationship between the North and the South. The results showed the existence of North-South linkages. Upon further testing using correlation matrices, we examine whether the linkages of the South with the North have weakened or not.